Efficacy of RNA interference using nanocarrier‐based transdermal dsRNA delivery system in the woolly apple aphid, Eriosoma lanigerum. Issue 2 (6th April 2022) - Guo, Yi; Fan, Yinjun; Teng, Ziwen; Wang, Lingyun; Tan, Xiumei; Wan, Fanghao; Zhou, Hongxu
Abstract: RNA interference (RNAi) is an essential approach for studying gene function and has been considered as a promising strategy for pest control. However, RNAi method has not been conducted in Woolly apple aphid ( Eriosoma lanigerum Hausmann), one of the most damaging apple pests in the world. In the study, we investigated the efficacy of RNAi of V‐ATPase subunit D ( ATPD ), an efficacious target for RNAi in other insects, in E. lanigerum by a transdermal double‐stranded RNA (dsRNA) delivery system with nanocarriers. Our results showed although topical application of dsATPD in E. lanigerum for 24 h produced 40.5% gene silencing, the additional help of nanocarriers extremely improved the interference efficiency with 98.5% gene silencing. Moreover, a 55.75% mortality was observed 5 days after topical application of nanocarriers and dsATPD, relative to the control (topical application of nanocarriers and double‐stranded green fluorescent protein [dsGFP]). The nanocarrier‐based transdermal dsRNA delivery system will promote the development of functional analysis of vital genes and also provide a potential target for RNAi‐based management of E. lanigerum . Abstract : The expression levels of V‐ATPase subunit D ( ATPD ) in Eriosoma lanigerum treated by dsATPD without nanocarriers were not significant difference relative to the aphids treated by double‐stranded green fluorescent protein (dsGFP). The expression levels of ATPD in aphids treated by nanocarriers + dsATPD were significantly reduced. The nanocarriers improved the efficiency of RNA interference (RNAi) and established RNAi method in E. lanigerum .